Coping strategies work stress among librarians in public library - Sembiring, Santana; Sitompul, Lola Utama; Mudana, I Wayan (Record and Library Journal, 2024)
Background of the study: Stress is an inseparable part of a person's professional life, including the librarian profession. One of the librarians who experiences work stress is the Librarian of the Regional Archives and Library Service (DAPD) of Buleleng Regency. Remember, DAPD is the only district-level public library operating in Buleleng. The number of activities carried out, the various characters of the users served, and the library's targets make DAPD Buleleng librarians very vulnerable to work stress. Purpose: The main aim of this research is to find out what the sources of work stress are and what strategies the DAPD Buleleng librarians use to overcome the work stress they experience. Method: This research uses a qualitative approach with descriptive analysis methods. The technique for determining informants uses purposive sampling techniques and data collection techniques using interviews, documentation, and literature study. Findings: From the research results, it is known that the source of work stress for DAPD Buleleng librarians is caused by two main situations, namely threatening situations such as excessive workload and unsuitable qualifications, inability to adapt to technology, attitudes, and character of librarians, and job targets that do not meet expectations; and challenging situations such as learning new things and maximizing efforts to achieve desired targets. The strategies used by DAPD librarians to deal with work stress are, sharing work, looking for a place that can restore their good mood, doing fun activities while at home, telling stories to colleagues, and praying to God. Conclusion: It turns out that the work stress experienced by librarians also has an impact on work life and personal life. The results of this research can be a reference source for libraries that librarians need to have an understanding of the ability to manage work stress.